(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The JASMINE model based on the prof. N.G. Iakovlev's model of the Arctic Ocean (FEMAO) is the software complex for simulating hydrodynamics and thermal dynamics of a sea; we use the White Sea as an example and also have tried to model other seas. JASMINE allows coupling with special purpose blocks, such as data assimilation or simulation of the sea ecosystem. For that we chose the mature BFM model of pelagic sea biochemistry. An important question is sensitivity of the model with respect to the outer forcing, such as synoptic data (air temperature and pressure, cloud cover, precipitation, wind), boundary values on liquid boundaries, river run-off, initial distributions of the tracers. The White Sea is a convenient model region for such investigation because of dominating tides; thus boundary values become important, while initial distribution is expected not to influence on the results in the long run, at least. The biochemical system also depends on the boundary conditions strongly, and also reacts on the forcing variations. We describe the response of the sea subsystems to different variations of forcing, show what values are crucial and what is not important.